Exchange Rate Policies of Developing Countries in the Context of External Shocks (Invited Lecture) (The Pakistan Development Review, 1986)
In the past decade a combination of events caused the international economic climate to become increasingly inimical to the growth and current account prospects of most developing countries. Worsening terms of trade, falling growth rates in industrial countries, and sharp changes in the availability of foreign financing that were accompanied by a dramatic increase in real interest rates on external borrowing, made the problem of economic management very difficult for policy-makers in the developing world. Adjusting to these shocks would have typically called for fiscal and monetary restraint to control both public and private spending, and more flexible exchange rate policy. Such a strategy, for one reason or another, was not followed by a number of developing countries, and consequently these countries experienced falling growth rates, rising inflation, and current account deficits that over time became unsustainable.